1974
DOI: 10.1136/hrt.36.6.588
|View full text |Cite
|
Sign up to set email alerts
|

Alpha- and beta-adrenergic receptor blockade in the treatment of hypertension.

Abstract: The effects of single and combined selective blockade of the sympathetic alpha-and beta-receptors were examined in patients with severe hypertension (diastolic pressure > I20 mmHg) uncomplicated by cardiac or renal failure. Given In uncomplicated essential hypertension the raised blood pressure is accompanied by a normal cardiac output (Taylor, Donald, and Bishop, I957). The increased peripheral resistance is uniformly distributed throughout all the regional circulations and resides predominantly in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…It is interesting to note that the circulating effects of oxprenolol plus phentolamine which were described by Majid et al, (1974) as being beneficial, occurred when phentolamine was being infused intravenously. Subsequent studies of chronically administered phentolamine have failed to confirm a beneficial antihypertensive effect (Johnson et al, 1976;Winchester et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that the circulating effects of oxprenolol plus phentolamine which were described by Majid et al, (1974) as being beneficial, occurred when phentolamine was being infused intravenously. Subsequent studies of chronically administered phentolamine have failed to confirm a beneficial antihypertensive effect (Johnson et al, 1976;Winchester et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…(Majid et al, 1974). However, using the same daily dose of oral phentolamine as used by Majid et al, (1974), two other groups of investigators failed to show any enhanced reduction in blood pressure from the phentolamine over that already achieved with a P-adrenoceptor blocking drug alone (Johnson, Labrooy & Munro-Faure, 1976;Winchester Ward McKillop & Kennedy 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we have shown that after oral administration labetalol induced ai-adrenoceptor antagonism to phenylephrine and in addition, a fall in resting supine pressure. Majid, Meeran, Sharma & Taylor (1974) have claimed that combined a-and ,B-adrenoceptor blockade is a highly desirable pharmacological basis for the treatment of hypertensive patients. Oral labetalol possessing these combined properties is likely therefore to produce reductions in blood pressure in hypertensive patients and this has been observed in treatment of hypertension for periods up to three years (Prichard et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It is also our experience that with oxprenololdiuretic regimen, in a small proportion of patients diastolic blood pressure fails to fall below levels which we have arbitrarily set at 100 mm,Hg. Majid, Meeran, Benaim, Sharma & Taylor (1974) (Galloway, Webster & Petrie, 1974) or in combination with ,B-adrenoceptor blockers (Johnson, Labrooy & Munro-Faure, 1974), however, has not been confirmed. Hydrallazine, a peripheral vasodilator, has been shown to be a useful agent in combination with a 3-adrenoceptor blocker-diuretic regimen (Aenishanslin, Pestalozzi-Kerpel, Duback, Imhof & Turri, 1972;Zacest, Gilmore & Koch-Weser, 1972).…”
Section: Introductionmentioning
confidence: 99%